A new species of Hemus (Majoidea: Majidae: Mithracinae) from the Pacific coast of Panamá, with a key to the genus - Windsor, Amanda M.; Felder, Darryl L. (Zootaxa, 2011)
A new species of spider crab, Hemus magalae n. sp. (Majidae), is described from a single male specimen from Islas de las Perlas, Pacific Ocean coast of Panamá. This species differs from its congeners with respect to many features of the carapace including mid-line elevation and lateral dentition. Hemus A. Milne-Edwards, 1875, now includes four species, three from coastal waters of the eastern Pacific Ocean and one from shallow waters in the tropical western Atlantic Ocean. A key to the Pacific and Atlantic species of Hemus is provided.